Hubungan antara Lama CPB dan Aortic Cross Clamp dengan Mortalitas dan Lama Rawat di ICU pada Pasien Pascaoperasi Katup Jantung di RSUP Dr. Sardjito - Anggraini, Diana; Widodo, Untung; Pratomo, Bhirowo Yudo (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Background: CPB (cardiopulmonary bypass) results a non physiologic circulation and AOX (aortic cross clamp) causes a hypoxic condition of myocard. The length of CPB and AOX are probably factors that influence the ICU outcome after valvular heart surgery. Objective: To determine whether CPB and AOX time have significant effect on postoperative ICU length of stay (LOS) and ICU mortality. Methods: Data were collected from hospital medical record from period 2010 until 2016. After inclusion and exclusion 57 patients were analyzed for mortality and LOS in ICU. Results: Among 57 patients, 9 (15%) had ICU stay > 3 days, the mean+SD CPB was 119,2+32,5 min, AOX 92,7+27,7 min, while 7 (12,3%) had mortality in ICU, the mean+SD CPB was 113,7+37,3 min, AOX 79,3+36 min. Statistically showed that there were no correlation between duration of CPB and AOX with LOS and mortality in ICU, but we found that increased LOS in patient with comorbid (CHF+other) (p=0,019 OR 7,7 CI 95% 1,39-42,66) while ICU mortality increased with value of APACHE II (p=0,015 OR 1,69 CI 95% 1,11-2,58). Conclusion: There were no correlation of CPB and AOX time against ICU LOS and in mortality ICU, but preoperative factor (CHF+other) and postoperative factor (APACHE II score) respectively have a factor correlation.